The role of administrative leadership in enhancing financial management activity - Aramco case study – - Khemili, Farid (Journal of Research in Finance and Accounting, 2025)
The study aimed to highlight the role that management leadership plays in promoting financial management activity, by demonstrating it in theory, and in practice by studying the case of Saudi Aramco. In order to achieve this, the descriptive approach was based on the theoretical and analytical approach to the case study by analysing some of the company's financial indicators. The study has reached to the basic conclusion that the Managing Leader plays a significant role in enhancing financial management activity, so the large share is that leadership work is around these activities because they are considered strategic activities through which organizations can continue and grow in a highly changing environment. That role has already been played by the leadership of Aramco, which has achieved high financial indicators.